2021
DOI: 10.1007/s10530-021-02623-3
|View full text |Cite
|
Sign up to set email alerts
|

A review of the impacts of biological invasions in South Africa

Abstract: Compared to other facets of invasion science, the impacts of biological invasions have been understudied, but many studies have been published in the last decade. This paper reviews the growing body of evidence of impacts of invasions in South Africa. We classified information for individual species into ten ecological and four social categories of impact. We also reviewed studies that upscaled this information to larger spatial scales, as well as progress with assigning invasive species to impact severity cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 117 publications
0
15
0
Order By: Relevance
“…In the absence of the rare and large indigenous fruits preferred by large mammal frugivores [57,[91][92][93][94], the baboons may opt for the large fruit crops of the alien plant species in gardens [35], which deprives the natural vegetation of seed dispersal services. This is concerning, since invasive plant species are known to alter habitat functionality and damage biodiversity [52,53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of the rare and large indigenous fruits preferred by large mammal frugivores [57,[91][92][93][94], the baboons may opt for the large fruit crops of the alien plant species in gardens [35], which deprives the natural vegetation of seed dispersal services. This is concerning, since invasive plant species are known to alter habitat functionality and damage biodiversity [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the fragmented state of the patches of Amathole indigenous forests in the Eastern Cape Province may increase certain species' vulnerability to extinction [45,51]. In addition, the invasion of alien and invasive plant species is an emerging conservation issue, and needs urgent attention, since invasive plants alter the structure and functionality of the habitat [52,53]. Consequently, understanding the role of baboons in the seed dispersal of alien and invasive plants is important for the conservation of the threatened indigenous Amathole Southern Mistbelt forest fragments in Hogsback in the Eastern Cape Province of South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive Alien Plants (IAPs) have a threat to the natural ecosystem and global biodiversity. Hence, it is considered one of the drivers of biodiversity and alters the ecosystem services and socio-economic conditions of an ecosystem [1][2][3][4]. The actors and information are a diverse and scattered, necessitating collaboration with regard to IAPs management.…”
Section: Introductionmentioning
confidence: 99%
“…IAPs management is critical on a global scale as invasive species have threatened native biodiversity and adversely impacted water resources and ecosystem services [1,3,4,6,[9][10][11][12]14,[16][17][18][19][20][21]. The Working for Water Programme in South Africa (1995) aimed to manage IAPs in order to achieve environmental (e.g., soil and water conservation, biodiversity conservation) and social (e.g., green job creation, skills and capacity building, and inclusion of marginalised and disadvantaged communities) sustainability goals [7,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, O. mykiss has established populations in the mountain streams and upland reservoirs in over 80% of the major drainage basins in the country (Weyl et al, 2020). There is, however, limited information on the impacts of O. mykiss invasions in South Africa (Zengeya et al, 2020;Van Wilgen et al, 2022). The few available studies have, however, shown that O. mykiss can cause a decline, and in some cases local extirpation of indigenous invertebrates, frogs, and fishes (Karssing et al, 2012;Rivers-Moore et al, 2013;Shelton et al, 2015a;Jackson et al, 2016;Weyl et al, 2020).…”
Section: Introductionmentioning
confidence: 99%